New Zealand's Counter Terrorism Strategy: A Critical Assessment - Ball R; Battersby J; Nelson N (Centre for Defence and Security Studies, Massey University)
In mid-February 2020 New Zealand released its long overdue ‘Countering terrorism and violent extremism national strategy.’ This article draws on the experience of three academic commentators who cast a critical eye over the document and whose respective thoughts are brought together here. The approach taken is to discuss the purpose and fundamentals of what strategy is to provide a framework with which to review New Zealand’s first publicly released counter-terrorism strategy. Unfortunately, this important and long overdue strategy, in the view of the authors, comes up well short of what it should be. The authors offer a challenge to New Zealand’s policy makers concerned with national security to seek more depth in the consideration of their approach, to present a strategy with less graphic design, more substantial discussion of the fundamental questions relating to the management of modern terrorism and violent extremism, and an appreciation of the nuanced New Zealand experience with political violence from late twentieth century to the present day.